Respostas

A melhor resposta!
  • Usuário do Brainly
2014-08-15T16:22:41-03:00
Temos que:

a) 10-2(y+1)+3(2-y)=y+1

Assim, 10-2y-2+6-3y=y+1,

ou seja, y+3y+2y=10-2+6-1.

Logo, 6y=13 e y=\dfrac{13}{6}

b) 8-(x+3)-(2x-1)=x+7

8-x-3-2x+1=x+7

x+2x+x=8-3+1-7

Logo, 4x=-1 e x=\dfrac{-1}{4}.
2 5 2
2014-08-15T18:34:20-03:00
A ) 10 - 2 ( y + 1 ) + 3 ( 2 - y ) = y + 1
10 - 2y - 2 + 6 - 3y = y + 1
- 2y - 3y - y = 1 - 10 + 2 - 6
- 6y = - 13 . ( - 1 )
6y = 13
y = 13/6 ou 2,16

B ) 8 - ( x + 3 ) - ( 2x - 1 ) = x + 7
8 - x - 3 - 2x + 1 = x + 7
- x - 2x - x = 7 - 8 + 3 - 1
- 4x = 1 . ( - 1 )
4x = - 1
x = - 1/4 ou 2,5 .
1 5 1